PENGARUH RESILIENSI DAN KEBAHAGIAAN TERHADAP KINERJA PERAWAT MELALUI KEPUASAN ERJA SEBAGAI VARIABEL INTERVENING PADA RUMAH SAKIT PONDOK INDAH - Siti Nuril Huda (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
The purpose of this study was to determine the effect of optimism and hope on the performance of nurses through satisfaction at Pondok Indah Hospital. The research methodology is a survey with quantitative analysis techniques and path analysis applied in hypothesis testing. The study was conducted on 226 nurses as a simple random sample. The results of the analysis and interpretation of the data show that: (1) Resilience has a direct and significant effect on job satisfaction, (2)Happiness have a direct and significant effect on job satisfaction, (3) Resilience has a direct and significant effect on nurse performance, (4) Happiness have a direct effect on performance nurses, (5) Satisfaction has a direct effect on nurse performance, (6) Resilience has an indirect effect on nurse performance and (7) Happiness has an indirect effect on nurse performance.